Redesigning the Colega Application Interface and Interaction Using the Learner-Centered Design Method - Aufar, Kasyfi Zulkaisi; Dian Martha, Ati Suci; Hadikusuma, Aristyo (Sinkron : jurnal dan penelitian teknik informatika, 2023)
In the rapid development of technology, almost all activities are carried out online, activities become timeless so that many students have difficulty in managing time between lectures and other activities. So that students must be able to organize their activity schedule, record tasks and activities that must be completed. One of the efforts that can be made is to use colega products which are technology products to remind activities. The purpose of this research is to redesign the Colega mobile application interface that is suitable and easy to use based on student needs to increase the level of usability with the learner-centered design method., this method is a design process that focuses on the needs of learner, by performing 5 stages, namely Specify the context of use, Specify user requirements, Product design solution, and Evaluate against user requirements. The product developed using this method, the principle of this method is a collaboration that allows learner to develop, test, and analyze their ideas for the product to be made. Interface design and interaction testing using the System Usability Scale. the results of usability testing on the interface obtained a value of 60.62 to 78.12. With the test results obtained an increase in value in the usability aspect. So it can be concluded that the usability value falls into the good and acceptable category.